Efektifitas Gelagar Pci Girder Bentang 40 Meter Jembatan Integral Multispan Pilar Tinggi - Akhbar, Try Kurniawan; Zakiyyah, Amirah; Puspitasari, Ira; Nurdin, Muhammad Irfan (Universitas Teuku Umar, 2025)
Integral bridges are a type of bridge designed without the use of expansion joints or dilation gaps, allowing the superstructure and substructure to act monolithically without relative movement. In Indonesia, the application of integral bridge concepts is limited. Generally, bridges in the country are designed using simple-span systems with conventional bearings, which, despite their straightforward construction, require periodic maintenance and replacement. Precast prestressed concrete (PCI) girders have been implemented in several integral bridge designs in Indonesia; however, their application is restricted, particularly for piers of considerable size or height. This study aims to determine the maximum pier height applicable for multispan integral bridges utilizing PCI girders commonly available in the market. The investigation focuses on girders with a span length of 40 meters, given their widespread use in Indonesia. Structural modeling was carried out for pier heights ranging from 30 to 60 meters, considering structural behavior during both construction stages and service conditions. The results indicate that for a pier height of 30 meters, the stresses in the PCI girder remain within permissible limits. However, when the pier height increases to 40 meters, the stress exceeded allowable thresholds. Therefore, the use of standard PCI girders with a 40-meter span under such conditions is not recommended unless supported by design modifications or advanced construction technologies. It is thus concluded that 40-meter PCI girders are effective for integral bridge applications with pier heights below 30 meters.